Estimation of Premium Reserves for Last Survivor Endowment Insurance Using the New Jersey Method - Bella Dwi Ananda; Fauziah Nur Fahirah Sudding (Journal of Actuarial, Finance, and Risk Management, 2023)
There are a few cases of life insurance firms going bankrupt due to mistakes when estimating premium reserves, causing companies unable to pay compensation to policyholders. This is caused when the number of claims submitted by the insured that must be paid exceeds the number of claims previously estimated. Situations like this can be anticipated if the insurance firm has a properly prepared and calculated reserve value. There are various types of life insurance, one of which is endowment life insurance. The purpose of this study is to calculate the amount of reserves adjusted for last survivor endowment life insurance using the New Jersey method. To compute reserves, first, researchers determine the benefits, then the annuity, and finally the annual premium. In the first year, the premium reserve value under the New Jersey method is zero. The New Jersey method begins premium reserves in the second year, for t years, with where reflecting the duration of the insurer's contract. Based on the data analysis performed, the value of the New Jersey reserves for the two insureds is determined by the length of the insurance contract and the age of the insured at the time of insurance. The value of reserves is seen based on the initial age of a person when starting insurance, the older the initial age of the insurance participant, the greater the amount of reserves obtained by the company. This research is expected can be a reference and help insurance field to estimate premium reserves.